THE EMBODIMENT OF SANDUNG AS AN ARTISTIC EXPRESSION FOR THE HINDU KAHARINGAN COMMUNITY IN PALANGKARAYA CITY (A.A.M DJELANTIK AESTHETIC THEORY STUDY) - Paramarta, Made; Lestari, Wahyu (Gorga : Jurnal Seni Rupa, 2024)
This research aims to examine Sandung as an artistic expression for the Hindu Kaharingan community in the city of Palangkaraya. Brisket is a container for the bones of deceased humans. The procession of placing human bones begins with the Tiwah ritual. The shape of the Sandung building varies according to its purpose for the dead, there are typical Dayak ornamental reliefs which are characteristic of Sandung. The shape, weight and appearance of the Sandung are very aesthetic. It is necessary to examine the actual form, arrangement based on facts in the field, what the atmosphere, ideas and messages are conveyed through the form of the Sandung, and what talents, skills, facilities and media are presented in the realization of the Sandung. The existence of Sandung contains an interconnected conception of art and religion, not only as a sacred place, but Sandung also has important meaning and function as a local cultural identity of the Kaharingan Hindu community in Palangkaraya City. This research uses A.A.M.'s aesthetic theory. Djelantik to dissect the manifestation of Sandung so that it can be studied in depth into a complete and in-depth article about Sandung. This research uses a qualitative method with a phenomenological approach using data collection techniques in the form of observation, interviews, documentation and literature review relevant to this research. local cultural identity of the Kaharingan Hindu community in the city of Palangkaraya. Based on the results of the analysis, this research is expected to contribute and contribute knowledge in the realization of Sandung for the Kaharingan Hindu community in the city of Palangkaraya.Keywords: embodiment, Sandung, aesthetic theory.